Investigating Problems of Inductive Approach in ELT During Early Career of Indonesian EFL Teachers - Leky, Abdul Majid S; Pratolo, Bambang Widi; Oktavianti, Ikmi Nur (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
The controversy of whether the English language should be taught inductively or deductively, implicitly or explicitly, consciously or subconsciously does not seem to arrive at its compromises yet. In the meantime, the methodology for English language teaching in the Indonesian EFL context has been ascribed to the inductive teaching paradigm. However, practical demands seem to have forced the teachers to develop their own teaching strategies. It is a serious problem for English teachers, especially during their early-career teaching. The current study aims to investigate problems in the implementation of inductive approaches along with some key strategies to cope with the problems. The data were obtained through a semi-structured interview involving two EFL teachers. The data was sourced from the participants' stated experiences and documents of their recorded classroom practice. The results yielded numerous contextual problems using an inductive approach, including students' capability, grammar complexity, achievement, and time insufficiency. The study also revealed key strategies teachers take, including re-adjusting their instruction procedures when an inductive approach is applied. The study implies that teachers and educational practitioners should be aware of redesigning existing learning methodologies that can be more contextualized and meet the learners' needs.